Plasma concentrations of vitamin B12 and folate and global cognitive function in an older population: cross-sectional findings from The Irish Longitudinal Study on Ageing (TILDA) - O'Connor, Deirdre; Kenny, Rose; Laird, Eamon; O'Halloran, Aisling; Molloy, Anne (My University, 2020)
The uncertainty surrounding high intakes of folic acid and associations with cognitive decline in older adults with low vitamin B12 status has been an obstacle to mandatory folic acid fortification for many years. We estimated the prevalence of combinations of low/normal/high vitamin B12 and folate status and compared associations with global cognitive function using two approaches, of individuals in a population-based study of those aged ≥50 years in the Republic of Ireland. Cross-sectional data from 3781 men and women from Wave 1 of The Irish Longitudinal Study on Ageing were analysed. Global cognitive function was assessed by the Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). Prevalence estimates for combinations of vitamin B12 (plasma vitamin B12 < or ≥258 pmol/l) and folate (plasma folate ≤ or >45·3 nmol/l) concentrations were generated. Negative binomial regression models were used to investigate the associations of vitamin B12 and folate status with global cognitive function. Of the participants, 1·5 % (n 51) had low vitamin B12 (<258 pmol/l) and high folate (>45·3 nmol/l) status. Global cognitive performance was not significantly reduced in these individuals when compared with those with normal status for both B-vitamins (n 2433). Those with normal vitamin B12/high folate status (7·6 %) had better cognitive performance (MMSE: incidence rate ratio (IRR) 0·82, 95 % CI 0·68, 0·99; P = 0·043, MoCA: IRR 0·89, 95 % CI 0·80, 0·99; P = 0·025). We demonstrated that high folate status was not associated with lower cognitive scores in older adults with low vitamin B12 status. These findings provide important safety information that could guide fortification policy recommendations in Europe. Keywords:
PUBLISHED
doi: doi:10.1017/S0007114520001427
Keywords: Ageing, Cognitive function, Epidemiology, Folate, Older people, Vitamin B12; Ageing